Semantic Consciousness and Inhabiting a Languacultural Community: A Sociocultural Approach - McCafferty, Steven (Status Quaestionis, 2020)
Vygotsky’s final ambition (see Veresov and Moc 2018) was to transform his previous work into a dynamic, interfunctional perspective of personhood centered on consciousness. What he was able to accomplish before his untimely demise focused primarily on the unity of cognition and affect. Human consciousness, as considered from the perspective of sociogenesis, necessarily involves how people come to inhabit the ecosocial world around them, moving from the social to the psychological. For Vygotsky, language is transformed in this process, becoming primarily semantic in inner speech, and together with perezhivanie, or how a person experiences an event/environment (interpretence), mediates consciousness. How we come to inhabit a language, culture, languaculture, or extemporaneous community, whether consisting of speakers of many languages or just one, necessarily involves our associations with language and experience at the intrapersonal level in formulating shared levels of interpretence interpersonally as well.